The impact of sanction and healthcare system reform on the healthcare performance and pharmaceutical market in Iran; 2001-2016 - Saman Zartab; Nasrin Nassiri Koopaei; Hadi Abbasian; Mansur Nassiri Koopaei; Nasser Nassiri Koopaei (Taylor & Francis Group, 2020)
Background Iranian government has introduced multiple healthcare system reforms during the last 30 years aiming at improving accessibility and affordability of care. Pharmaceutical products are one of the major sources of financial burden on the healthcare system. The healthcare system and pharmaceutical sector have been balanced out by the partially counteracting effects of the HSEP (Health sector evolution plan) and the imposed sanctions. Methods This research investigates the healthcare system performance as well as the pharmaceutical market trend mostly based on the financial criteria from 2001. The correlation between the two change patterns was studied to understand the underlying driving market forces. Results During 2001 to 2013, total health expenditure has grown 25.6% in average. THE (Total health expenditure) share of the GDP remains between 6-7%, while the out of pocket payment has dropped to 37% in 2015 from 57% in 2001, and most health services been directed to the inpatient facilities. Iranian pharmaceutical market has grown rapidly in recent years and grew 28.38% per year and drug consumption per capita reached 34.43$ from 2.28$. However, the import drove most of the market expansion. Noteworthy, the share of pharmaceuticals from THE has also increased. Conclusions It is concluded that the sanctions and HSEP have enforced partially counteracting forces on the pharmaceutical market to maintain its consistent growing trend.